Functional Implications of Cathelicidin Antimicrobial Protein in Breast Cancer and Tumor-Associated Macrophage Microenvironment - Chen, Jiawei (Biomolecules, 2020)
It is well-established that tumor-associated macrophages (TAMs) play an important role in breast cancer development. Accumulating evidence suggested that human cathelicidin antimicrobial protein (CAMP), which is mainly expressed in host defense cells such as macrophages, is crucial not only in combating microorganisms but also promoting tumor growth. Here we report the interaction of CAMP with TAMs in breast cancer. CAMP expression was upregulated in cancer tissues and in the circulation of breast cancer patients. Surgical removal of tumor decreased CAMP peptide serum level. Knockdown of CAMP decreased cell proliferation and migration/invasion ability in breast cancer cells. CAMP expression was altered during macrophage M1/M2 polarization and was expressed predominantly in M2 phenotype. In addition, breast cancer cells co-cultured with macrophages upregulated CAMP expression and also increased cancer cell viability. Xenograft tumors reduced significantly upon CAMP receptor antagonist treatment. Our data implicated that CAMP confers an oncogenic role in breast cancer and plays an important role in the tumor microenvironment between TAMs and breast cancer cells, and blocking the interaction between them would provide a novel therapeutic option for this malignant disease.